PROBLEMATIKA MEDIASI DALAM KASUS PERCERAIAN DI MAHKAMAH SYAR’IYAH LANGSA - Wirda Hairani dan syawaluddin Islami (Hukum Keluarga Islam IAIN LANGSA, 2018)
This study wants to see the problem of mediation in divorce cases at the Langsa Mahkamah Syar'iyah. The procedure for conducting mediation in the court as regulated in PERMA Number 02 of 2003 was found to be a problem originating from PERMA itself. Then MA revised PERMA Number 02 of 2003 with PERMA Number 01 of 2008. After a long period of time it turned out that PERMA Number 01 of 2008 had its shortcomings, namely the mediation procedure in the court had not optimally fulfilled the need for mediation and increased the success of mediation in court. The Supreme Court decided to issue the latest regulation again, namely PERMA Number 01 of 2016.